Hidden stories : exploring teachers’ experiences of family violence response and inter-agency collaboration in schools : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Auckland, New Zealand - Neilson-Dyer, Susan (Massey University, 2025)
The introduction of the Family Violence Act (2018) marked a significant shift in legislative guidance for information-sharing and inter-agency collaboration, for the first time, naming schools as social agencies taking an active, collaborative role in family violence response, opening spaces to privilege the knowledge of teachers, positioning them as valuable stakeholders in inter-agency working. The current research aimed to explore teachers experiences of family violence response and collaborative opportunities through listening to the lived experiences of six primary school teachers who worked prior to and since the introduction of the Family Violence Act (2018), analysed using Interpretative Phenomenological Analysis. The identified themes of Spaces and Islands, Doing What is Right and Best, and Travelling with the Trauma revealed the isolation, institutional and professional limitations, and pain teachers experience when supporting children who have experienced family violence in their classroom due to a lack of information-sharing capabilities and collaborative interagency networks of support that persist despite the potentials the Family Violence Act (2018). The adaptive and creative strategies teachers employ to protect and support their students was also acknowledged, where they do what they can with heart and with passion within the limitations and constraints they face, at times placing themselves at risk to protect their students. The findings from this study highlight the commitment of teachers to student wellbeing, and the under-utilised, detailed student knowledge they can contribute to inter-agency family violence response measures in Aotearoa. Systemic change is required to recognise teachers and schools as valuable stakeholders in inter-agency networks of family violence response, and to mobilise their expert knowledge and experience to better support and protect children experiencing family violence in our communities. As the first research study in Aotearoa New Zealand to explore teachers’ lived experiences of family violence response, it is recommended that further study of teachers’ lived experience is required to continue contributing to our collective knowledge of inter-agency family violence response.
Keywords: 520303 Counselling psychology